If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + 2y + -2 = 9y + 12 + -6y Reorder the terms: 5 + -2 + 2y = 9y + 12 + -6y Combine like terms: 5 + -2 = 3 3 + 2y = 9y + 12 + -6y Reorder the terms: 3 + 2y = 12 + 9y + -6y Combine like terms: 9y + -6y = 3y 3 + 2y = 12 + 3y Solving 3 + 2y = 12 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. 3 + 2y + -3y = 12 + 3y + -3y Combine like terms: 2y + -3y = -1y 3 + -1y = 12 + 3y + -3y Combine like terms: 3y + -3y = 0 3 + -1y = 12 + 0 3 + -1y = 12 Add '-3' to each side of the equation. 3 + -3 + -1y = 12 + -3 Combine like terms: 3 + -3 = 0 0 + -1y = 12 + -3 -1y = 12 + -3 Combine like terms: 12 + -3 = 9 -1y = 9 Divide each side by '-1'. y = -9 Simplifying y = -9
| 17x+8+9x-9=2x+23 | | 3x+1/3-13/2=1-x/4 | | 2(x-3)=-10 | | -14=8+x | | 2-5(3-y)=2-(4-5y) | | 48=2x-6 | | 1=5p-2-4p | | 4=7x | | 2(6-8x)=4(2x-3) | | -11x+22=45 | | r+0.27=-0.59 | | 6(-x-2)=48 | | r+0.27=-0.25 | | -7x+6=48 | | 2(x+1)=3(x+7)-12 | | 2x/3=6-x/4 | | 25x^2-129=0 | | 3(2+x)=2(2+x) | | x^3+10x^2+13x+24=0 | | 2(x+1)=3(x+7) | | x-2(6)=2 | | 3s^2=2s^2+1 | | 5x+4=-x-20 | | -10x-4x+13x=0-7 | | 5x-7(x-4)=51 | | 14x=(5x+14) | | y=xk | | .3.7(-83x-3)=3.7(7x-30) | | 3x+61=6x-11 | | 245-2x=43x+15 | | 5x-x=14*5 | | 6.7=-3.2+x |